Shape resonance of sulphur dioxide anion excited states using the CAP-CIP-FSMRCCSD method - Basumallick, Suhita; Bhattacharya, Sumantra; Jana, Irina; Vaval, Nayana; Pal, Sourav (Molecular Physics, 2020)
We have studied the shape resonance of excited states of sulphur dioxide (SO2) anion by using the correlated independent particle Fock space multi-reference coupled cluster (CAP-CIP-FSMRCCSD) method augmented by complex absorption potential. These resonant states have been trapped experimentally in recent years by electron collision. In particular, we have investigated e(-)-SO2 scattering and computed the negative-ion resonance states of the anion responsible for the two resonances around 4.45 and 6.56 eV and compared the results with the existing experimental observations. From the computational results using the CAP-CIP-FSMRCCSD method, it has been observed that both the resonances near 4.45 and 6.56 eV result from A(1) symmetries. [GRAPHICS] .
Keywords: CAP augmented correlated independent particle (CAP-CIP-FSMRCCSD); complex absorption potential (CAP); coupled cluster; Fock space multireference coupled cluster (FSMRCCSD); shape resonance